The Effect of Profitability, Leverage, Liquidity, and Firm Size on Earnings Management with Gender Diversity as a Moderating Variable - Astuti, Melinda; Bertuah, Eka (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the effect of firm characteristics – profitability, leverage, liquidity, and firm size – on earnings management, with gender diversity on the board of directors as a moderating variable. Using panel data from food and beverage industry companies listed on the Indonesia Stock Exchange (IDX) from 2019 – 2023, the study finds that profitability has a positive and significant effect on earnings management, while leverage, liquidity, and firm size have no significant effect. Gender diversity negatively moderate the relationship between profitability and earnings management, indicating that the presence of women on the board can reduce earnings manipulation during profitability. In contrast, gender diversity positively moderate the firm effect of firm size, suggesting that in larger firms, it may strengthen the tendency toward earnings management. Gender diversity does not moderate the effect of leverage and liquidity on earnings management. These findings contribute to agency theory by demonstrating that profitability creates an incentive misalignment between managers and shareholders, which can lead to earnings manipulation. However, gender diversity can strengthen monitoring and reduce agency conflicts, though its effectiveness varies by context. These results imply that the effectiveness of gender diversity as a governance mechanism depends on specific firm conditions.